Eliciting and modeling the requirements for an online data archival management system - Mkpojiogu E.O.C.; Efeakusu G.; Hussain A.; Hashim W. (Science and Engineering Research Support Society, 2023)
Information is an integral part of any persons or organisations life as important decisions are made based on them. As such there is a need to properly store/achieve, manage and easily retrieve important and sensitive information when necessary. However, the use of papers and manually sorting, storing, searching, retrieving and moving files is tedious, time-consuming and not very efficient. The purpose of this study is to elicit and model requirements for a data archival management system to be used in Veritas University, Abuja. The system when implemented will solve a good number of the complications involved in manually archiving and managing files in the institution. The requirements elicitation was carried out via interviews while the requirements modelling were done using UML. 2020 SERSC.